Vascularity and Dynamic Contrast-Enhanced Breast Magnetic Resonance Imaging - Frankhouser, David E.; Dietze, Eric; Mahabal, Ashish; Seewaldt, Victoria L. (Frontiers in Radiology, 2021)
Angiogenesis is a key step in the initiation and progression of an invasive breast cancer. High microvessel density by morphological characterization predicts metastasis and poor survival in women with invasive breast cancers. However, morphologic characterization is subject to variability and only can evaluate a limited portion of an invasive breast cancer. Consequently, breast Magnetic Resonance Imaging (MRI) is currently being evaluated to assess vascularity. Recently, through the new field of radiomics, dynamic contrast enhanced (DCE)-MRI is being used to evaluate vascular density, vascular morphology, and detection of aggressive breast cancer biology. While DCE-MRI is a highly sensitive tool, there are specific features that limit computational evaluation of blood vessels. These include 1) DCE-MRI evaluates gadolinium contrast and does not directly evaluate biology, 2) the resolution of DCE-MRI is insufficient for imaging small blood vessels, and 3) DCE-MRI images are very difficult to co-register. Here we review computational approaches for detection and analysis of blood vessels in DCE-MRI images and present some of the strategies we have developed for co-registry of DCE-MRI images and early detection of vascularization.